Trajectories of Sleep and Its Predictors in the First Year Following Traumatic Brain Injury. Issue 4 (July 2015) - Chen, Pin-Yuan; Tsai, Pei-Shan; Chen, Ning-Hung; Chaung, Li-Pang; Lee, Cheng-Chi; Chen, Ching-Chang; Chiu, Hsiao-Ting; Lu, Yu-Jen; Wei, Kuo-Chen; Chiu, Hsiao-Yean
Abstract : Objectives: To examine how sleep patterns change over the first year following traumatic brain injury (TBI) and to determine whether specific demographic and disease characteristics predict the trajectories of sleep. Design: Prospective study. Participants: Fifty-three patients with first-ever mild to severe TBI. Main Measurements: Sleep measured by actigraphy for 7 consecutive days in the first, third, sixth, and twelfth months following TBI: Chinese versions of Beck Anxiety Inventory and Beck Depression Inventory-II (CBDI-II) measured at the same time points. Data were analyzed with a linear mixed model. Results: Sleep efficiency (the ratio of sleep time to the total time spent in bed) showed a significant upward trend during the study period. Scores on the Chinese version of the Beck Anxiety Inventory and the CBDI-II as well as the use of analgesics significantly predicted the slope of change in sleep efficiency over time. Conclusions: Poor sleep efficiency is a common symptom in the first year among patients with first-ever TBI. Healthcare providers should consider both mental health and pain issues when dealing with sleep complaints in patients with TBI.